Employment status and work competencies of TESDA-PSAT graduates : a tracer study - Deogracias, Mely P. (Pangasinan : [s.n.], 2013)
The aim of this study was to determine the employment status of TESDA-PSAT graduates and how their work competencies are perceived by employees. This study employed descriptive survey design. Data gathering was done by having the respondents answer survey questionnaires. There were two groups of respondents who participated this study: 207 graduates of PSAT during the years 2009 and 2010 and 32 employers representing the business establishments where the graduates have sought employment.
Bibliography: pages 109-112.
CHED-La Union
Keywords: Employment